Prevalence of Coronary Artery Lesion(S) in Pati ents Aged 40-50 Years Undergoing Rheumatic Valvular Surgery - Elameen, Sameh; Salem, Alsayed; Abdelgawad, Ahmed; El shemy, Ahmed; Taha, Saber; Abdelsalam, Islam (European Scientific Journal, ESJ, 2018)
Objective: To determine the prevalence of coronary artery disease in patients undergoing valve surgery for rheumatic heart disease between age 40-50 years, usefulness, and indication of pre-operative coronary angiography. Methods: This is an observational prospective study that took place in 2 hospitals (National Heart Institute and Nasser Institute) within the period starting from January 2013 to January 2015. We included 454 rheumatic patients that were admitted for elective primary mitral, aortic or double valve surgery, and that had a coronary angiogram in their regular preoperative workup. All coronary angiographies were performed by injecting right and left coronaries by using 80-100 ml of iodinated contrast to obtain the standard views of both right and left coronaries using Philips or Siemens machines in both hospitals. Coronary artery disease (CAD) of 50% is considered to be a positive finding. Results: There was no correlation between rheumatic heart disease in this age group and CAD as only 1.76% had the significant stenosis. Male gender, family history of CAD, age above 45yrs, hypertension, and smoking showed significant correlation with the CAD in this study. Conclusion: Our results suggest that the overall prevalence of coronary artery disease in patients undergoing rheumatic valve surgery in our population is not comparable with the prevalence reported in international data. So, multicenter studies are needed in developing countries to set their own guidelines. Therefore, our study can be the nucleus for these guidelines in our country.